The Effect of Coaching and Discipline on Managerial Employee Performance Mediated by Employee Engagement Transportation Industry - Novembriani Irenita; Lily Yuntina; Fasida Dharma Yudastoro; Erni Pratiwi Perwitasari; Mochammad Subagio (Green Publisher, 2024)
The article on the influence of coaching and discipline on managerial employee performance which is mediated by employee engagement is a scientific literature article within the scope of human resource management science. The purpose of this writing is to build a hypothesis of the influence between variables which can later be used for further research within the scope of human resource management. The research method used is descriptive qualitative. Data was obtained from previous research that is relevant to this research and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Coaching influences employee engagement; 2) Discipline influences employee engagement; 3) Coaching influences the performance of managerial employees; 4) Discipline influences the performance of managerial employees; 5) Employee engagement influences the performance of managerial employees; 6) Coaching managerial influences employee performance through employee engagement; and 7) Discipline influences managerial employee performance through employee engagement.